Prognostic factors of ado-trastuzumab emtansine treatment in patients with metastatic HER-2 positive breast cancer. (April 2021) - Tataroglu Ozyukseler, Deniz; Basak, Mustafa; Ay, Seval; Koseoglu, Aygül; Arıcı, Serdar; Oyman, Abdilkerim; Sürmeli, Heves; Turan, Merve; Turan, Nedim; Odabaş, Hatice; E Yıldırım, Mahmut
Background: Ado-trastuzumab emtansine is an antibody-drug conjugate that combines the cytotoxic activity of emtansine with human epidermal growth factor receptor 2-targeted antitumor features of trastuzumab. Objective: We conducted a study of metastatic breast cancer patients treated with trastuzumab emtansine. By evaluating progression-free survival, overall survival, and response rates, we aimed to find prognostic factors of trastuzumab emtansine treatment. Methods: Our study is a single-center, retrospective, observational study. We have clinical data from 78 patients treated with trastuzumab emtansine for metastatic breast cancer, from May 2016 through May 2019, at Kartal Dr Lutfi Kirdar Education and Research Hospital, Medical Oncology Department. Our objective is to assess the survival and response rates in trastuzumab emtansine-treated individuals and the factors associated with survival. The factors we analyzed were cancer antigen 15-3 sensitivity, Eastern Cooperative Oncology Group-Performance Status, presence or absence of visceral metastases, presence or absence of cranial metastases, and treatment-associated thrombocytopenia. Results: Among 78 patients, median progression-free survival was 7.8 months, and overall survival was 21.1 months. Twenty of the patients had an objective tumor response. The results showed that trastuzumab emtansine was tolerable with a manageable safety profile and consistent with the results of the previous literature. Mostly seen adverse events were anemia, thrombocytopenia, fatigue, and increased levels of alkaline phosphatase. Patients with Eastern Cooperative Oncology Group-Performance Status = 2 had worse progression-free survival and overall survival compared to ones with Eastern Cooperative Oncology Group-Performance Status < 2; progression-free survival and overall survival are worse in cancer antigen 15-3-sensitive breast cancer patients. According to our findings, treatment-associated thrombocytopenia was a significant prognostic factor for survival. Patients with thrombocytopenia had 12 months progression-free survival, whereas patients without thrombocytopenia had only 4.1 months progression-free survival. In like manner, overall survival was much better in the thrombocytopenia-experienced patients as 29.5 versus 11.8 months. Conclusions: Trastuzumab emtansine prolongs progression-free survival and overall survival with a manageable safety profile. Thrombocytopenia, Eastern Cooperative Oncology Group-Performance Status, and cancer antigen 15-3 are correlated with progression-free survival and/or overall survival.